Problems of Tourism Development on a Regional Scale - Zajadacz, Alina; Kosińska, Agata (My University, 2016)
In the first part of the study the types of barriers to tourism development that may occur during the planning phase of this development, and in the phase of implementation of these plans, including the endogenous and exogenous barriers, were presented. The second part presents the results of research on the factors hindering the development of tourism identified in the selected region of Wielkopolska Province (Poland). The article presents detailed description of tourism barriers categories, which include: political and legal, economic, infrastructure, social, geographical and organizational problems. In the final part article presents a difference in the understanding of problems depending on the stakeholder groups, which leads to the conclusion that in order to be able to specifically identify problematic issues opinion of different stakeholders categories should be recognized. Only such action can lead to the construction of the development strategy, which will not have any areas of uncertainty (i.e. «gaps» in the identifying problem areas).
Keywords: obstacles to tourism development; tourism development barriers; strategic planning; implementation of development plans; Wielkopolska Province